RAMSEY COUNTY PROPOSED SMOKING BAN - BROZEK, MICHAEL; NELSON, DAN (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Memorandum from Michael Brozek and Dan Nelson to Paul Emrick regarding the Ramsey County (Minnesota) proposed smoking ban. Summarizes Ramsey County Board hearing. Explains the Ramsey County Board’s decision prior to the hearing not to vote on the proposal. Predicts that a total smoking ban will not occur.